2019
DOI: 10.1016/s1473-3099(18)30512-7
|View full text |Cite
|
Sign up to set email alerts
|

The potential effect of improved provision of rabies post-exposure prophylaxis in Gavi-eligible countries: a modelling study

Abstract: SummaryBackgroundTens of thousands of people die from dog-mediated rabies annually. Deaths can be prevented through post-exposure prophylaxis for people who have been bitten, and the disease eliminated through dog vaccination. Current post-exposure prophylaxis use saves many lives, but availability remains poor in many rabies-endemic countries due to high costs, poor access, and supply.MethodsWe developed epidemiological and economic models to investigate the effect of an investment in post-exposure prophylaxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 22 publications
4
55
0
2
Order By: Relevance
“…Those who do initiate PEP swiftly often do not complete it [12,13]. In other countries, various factors contributed to limited or delayed treatment seeking, including the lack of perceived need for immediate treatment after exposure [14], preference for traditional medicine, giving priority to earning a livelihood over seeking care [15], limited supply at health facilities [16] and increasingly, vaccine hesitancy [17,18]. Some people reported that rabies vaccine injections were painful and difficult to tolerate [19]; parents reported desperation when they see their children in pain because of a vaccine [17].…”
Section: Introductionmentioning
confidence: 99%
“…Those who do initiate PEP swiftly often do not complete it [12,13]. In other countries, various factors contributed to limited or delayed treatment seeking, including the lack of perceived need for immediate treatment after exposure [14], preference for traditional medicine, giving priority to earning a livelihood over seeking care [15], limited supply at health facilities [16] and increasingly, vaccine hesitancy [17,18]. Some people reported that rabies vaccine injections were painful and difficult to tolerate [19]; parents reported desperation when they see their children in pain because of a vaccine [17].…”
Section: Introductionmentioning
confidence: 99%
“…Global elimination of dog-mediated human rabies deaths is likely to require improved access and adherence to human rabies vaccines. Increasing access to human rabies vaccine is thought to be much more feasible on a global scale under the context of an IBCM-strategy [20]. This study has shown that IBCM can be successful enacted in a resource limited setting and has the potential to significantly reduce human rabies vaccine costs; costs that will ideally be re-allocated to dog vaccination activities to achieve permanent canine rabies elimination.…”
Section: Discussionmentioning
confidence: 93%
“…Globally, tens of thousands of people die each year from rabies virus infection due to lack of appropriate post-exposure prophylaxis after a bite from a rabid dog. Increased access to PEP has been proposed as one means of reducing human rabies deaths, particularly when used in combination with mass dog vaccination strategies 20 . However, given that dog bites are a relatively common event in many countries, and the cause of dog bites is rarely because the animal is rabid, unfettered use of rabies PEP in the absence of a risk-based approach may lead to very high program costs and frequent supply shortages 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Progressively switching over to cost-effective WHO-recommended intradermal PEP regimens, improving PEP availability and accessibility, scaled-up mass canine vaccination, and heightened public awareness of rabies PEP are suggested as central policies for eliminating human deaths from dog-mediated rabies [10,12,13]. Economic gains made by healthcare providers via the reduction of procurement costs is a major driver for policy makers for implementing effective policies [10,13].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of new clinical evidence and public health needs, WHO recently recommended the dose-sparing abridged one-week intradermal regimen for rabies PEP [11,12]. A study utilizing epidemiological and economic models projected that a switchover to the dose-sparing abridged one-week intradermal regimen along with Gavi (The Vaccine Alliance) investment for improving PEP accessibility and free provision would cost-effectively reduce the disease burden without much change in the vaccine requirement [13]. However, the dose-sparing abridged one-week intradermal regimen is yet to be approved by the DCGI for routine use in India.…”
Section: Introductionmentioning
confidence: 99%